2015
DOI: 10.1002/ange.201409499
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Benzene or Naphthalene Binding to Palladium Cluster Sites by the Backside‐Ligand Effect

Abstract: The backside-ligand modulation strategy to enhance the substrate binding property of Pd clusters is reported. The benzene or naphthalene binding ability of Pd 3 or Pd 4 clusters is enhanced significantly by the backside cyclooctatetraene ligand, leading to the formation of the first solution-stable benzene-or naphthalene Pd clusters. The present results imply that the ligand design of the metal clusters, especially for the backside ligand of the metal cluster site, is crucial to acquire a desired reactivity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…In fact, known examples of ligand‐unsupported metal–metal coupling involving metallocenes of transition metals are reported in a manner that two odd‐electron metal moieties are bonded through σ‐type interaction, such as d 1 –d 7 Cp 2 ClZr‐RuCp(CO) 2 , d 5 –d 5 [Cp 2 Ru‐RuCp 2 ] 2+ , [Cp 2 Os‐OsCp 2 ] 2+ , Cp 2 Re‐ReCp 2 , and d 5 –d 1 Cp 2 Re‐YCp 2 . For sandwich clusters, our group has previously shown that the σ‐type M−M coupling between the odd‐electron [Pd 3 Tr 2 ] + or [Pd 3 (CHT) 2 ] + species (Tr=C 7 H 7 , CHT=C 7 H 8 ) gives [Tr 2 Pd 3 ‐Pd 3 Tr 2 ] 2+ or [(CHT) 2 Pd 3 ‐Pd 3 (CHT) 2 ] 2+ frameworks . The present results showed that a metal–metal edge of an even‐electron sandwich cluster becomes a unique docking site for an even‐electron metal moiety through π‐type interaction.…”
Section: Figuresupporting
confidence: 56%
See 2 more Smart Citations
“…In fact, known examples of ligand‐unsupported metal–metal coupling involving metallocenes of transition metals are reported in a manner that two odd‐electron metal moieties are bonded through σ‐type interaction, such as d 1 –d 7 Cp 2 ClZr‐RuCp(CO) 2 , d 5 –d 5 [Cp 2 Ru‐RuCp 2 ] 2+ , [Cp 2 Os‐OsCp 2 ] 2+ , Cp 2 Re‐ReCp 2 , and d 5 –d 1 Cp 2 Re‐YCp 2 . For sandwich clusters, our group has previously shown that the σ‐type M−M coupling between the odd‐electron [Pd 3 Tr 2 ] + or [Pd 3 (CHT) 2 ] + species (Tr=C 7 H 7 , CHT=C 7 H 8 ) gives [Tr 2 Pd 3 ‐Pd 3 Tr 2 ] 2+ or [(CHT) 2 Pd 3 ‐Pd 3 (CHT) 2 ] 2+ frameworks . The present results showed that a metal–metal edge of an even‐electron sandwich cluster becomes a unique docking site for an even‐electron metal moiety through π‐type interaction.…”
Section: Figuresupporting
confidence: 56%
“…TheP d 4 sheet sandwich complex 1 features its intriguing square M 4 sheet sandwich structure and coordinatively unsaturated nature.F or the latter, it has been shown that 1 accommodates at least two PPh 3 ligands at the equatorial coordination sites. [6] Thecoordinatively unsaturated nature of 1 was further confirmed here by synthesis and structural characterization of the bis-adduct of P(OPh) 3 [a] The tetranuclear binding of cycloheptatrienyl has not been observed in bis-ligated sandwich complexes, but was recently observed in hexakis-ligated 3D-sandwich clusters. [25] [b] The pentanuclearbinding of cyclononatetraenyl is unprecedented.…”
mentioning
confidence: 71%
See 1 more Smart Citation